2017
DOI: 10.1007/s40520-017-0813-9
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic characteristics and factors associated with hospitalization in psychiatry of old age patients: an international comparison between Ireland and Turkey

Abstract: It is possible to infer that independent from the cultural diversities, living arrangement is a consistent entity to influence length of hospital stay in older adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Another study by Bo et al (2016) reported that greater CI was independently associated with prolonged LOS among patients admitted from home; however, for patients admitted from intermediate or long-term care facilities, it was lower CI that was independently associated with prolonged LOS. In a study comparing patients discharged from psychiatric hospitals in Turkey with similar patients in Ireland, the presence of delirium or dementia was not associated with LOS, but the proportion of such patients in the sample was low: 13.6 per cent in Turkey and 25.5 per cent in Ireland; the only factor significantly associated with LOS was living alone (Carpar et al, 2018). In the last mixed-results study, a trend towards longer stay was seen for dementia patients, which was only significant in the subgroup who lived with a family member (11.61 vs. 7.55 days, p = 0.002) (Ahern et al, 2019).…”
Section: Association Between Cognitive Impairment and Los Or Ddmentioning
confidence: 98%
“…Another study by Bo et al (2016) reported that greater CI was independently associated with prolonged LOS among patients admitted from home; however, for patients admitted from intermediate or long-term care facilities, it was lower CI that was independently associated with prolonged LOS. In a study comparing patients discharged from psychiatric hospitals in Turkey with similar patients in Ireland, the presence of delirium or dementia was not associated with LOS, but the proportion of such patients in the sample was low: 13.6 per cent in Turkey and 25.5 per cent in Ireland; the only factor significantly associated with LOS was living alone (Carpar et al, 2018). In the last mixed-results study, a trend towards longer stay was seen for dementia patients, which was only significant in the subgroup who lived with a family member (11.61 vs. 7.55 days, p = 0.002) (Ahern et al, 2019).…”
Section: Association Between Cognitive Impairment and Los Or Ddmentioning
confidence: 98%
“…Older adults are increasingly living alone [12], which is associated with a higher risk of ED admissions [13][14][15][16], longer inpatient days [17][18][19][20][21][22] and higher inpatient costs [19]. Since older adults living alone are not able to draw support as immediately as those living with others, they could rely more on acute tertiary services when emergencies arise [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…29 In other studies reporting on admissions of older adults because of suicide risk, the rates vary from 13.3% 30 to 48.1%. 31 However, these studies were set in specialised psychogeriatric units with differing intake criteria, making comparison with our findings difficult. Further, we found that although the patients in the PPH group were more likely to report suicidal ideation at the time of admission, the patients in the NPH group were more likely to have made a suicide attempt, the latter finding being robust for sensitivity analyses controlling for differences in age and organic disorders.…”
Section: Discussionmentioning
confidence: 93%